A model of soft skill instruction based on the local culture for vocational teacher candidates in North Sumatra - Muhammad Amin; Zamroni Zamroni; Herminarto Sofyan (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
This research aims to (1) find an instructional model as a guide for soft skill instruction in LPTK from the aspects of planning, implementation, and evaluation; and (2) determine the effectiveness of the use of soft skill instruction model for vocational teacher candidates. This study is a research and development with the steps adapted from Borg & Gall. The research was conducted through five stages including, preliminary studies, developing the initial model, expert validation, limited testing, and expanded trials. The data collection used observation sheets, questionnaires, and assessment sheets. The data analysis was performed with different test by Wilcoxon Signed Ranks Test and Kruskal Wallis Test. The results of the research show that: (1) the instruction model developed are in the category of very valid based on the assessment of experts team, and the level of application suitability is at a very appropriate categories according to user ratings; and (2) the instruction model developed can enhance the ability soft skills of vocational student teachers candidate significantly (p = 0.000), and improve student results were significantly (p = 0.014).